Efficient artificial light-harvesting systems based on aggregation-induced emission in supramolecular gels. Issue 34 (19th August 2021) - Ma, Xinxian; Qiao, Bo; Yue, Jinlong; Yu, JingJing; Geng, Yutao; Lai, Yingshan; Feng, Enke; Han, Xinning; Liu, Minghua
Abstract : Based on a acyl hydrazone supramolecular organogel with rhodamine B and acridine red as acceptors. Both the G2@gel-RhB and G2@gel-acridine red systems showed high levels of energy-transfer efficiency and high fluorescence quantum yields. Abstract : Based on a new designed acyl hydrazone gelator (G2), we developed a supramolecular organogel in glycol with two different hydrophobic fluorescent dyes, namely rhodamine B (RhB) and acridine red, as acceptors. Both the G2@gel-RhB and G2@gel-acridine red systems showed high levels of energy-transfer efficiency and high fluorescence quantum yields.